Financial measures of the non-shelter benefits of neighbourhood renewal programs; a quasi-experimental approach - Wood, Gavin; Cigdem, M. (2014)
In this paper we implement a robust quasi-experimental methodological design to evaluate Victoria's Neighbourhood Renewal (NR) program. NR's main objective is to tackle disadvantage in neighbourhood areas with concentrations of public housing. This paper draws on housing attributes recorded in the Victoria-General's Transactions and Valuations datasets and applies propensity score techniques combined with a difference-in-difference estimator to measure the impact of seven NR program sites. These quantitative techniques are used to arrive at financial measures of the non-shelter benefits (housing externalities) generated by renewal programs. It is the first study to apply quasi-experimental techniques in Australian housing and urban studies. Our findings suggest that five NR sites generate a housing externality benefit of $372m, and an increase in total stamp duty revenues of $5.3m. Benefit/cost measures indicate a positive multiple with average externality gains of $2.2 for every dollar invested over a nearly 10 year period 2002-2011.